The Effect of Using Guessing Game Media Themed Local Tourism on Students’ Achievement in Writing Narrative Text - Daulay, Irma Khoirot; Hasugian, Kristina Br. (Budapest International Research and Critics University, 2021)
The research was conducted to discover the effect of using guessing game media themed local tourism on students’ achievement in writing narrative text. The research was conducted to the grade tenth students of SMA GKPI PAMEN. This research used experimental design. To collect the data 2 classes get involved. There are X-1 as the experimental class that taught by using the guessing game media and X-2 as the control class that taught using the conventional method. The students consist of 30 students. In experimental class, the mean score for the pre-test was 45,46 and the score of post-test was 81,4. In control class, the mean of pre-test score was 46,5 and the post-test was 73,06. The analysis of the t-test showed that tscore > ttable or 3,53 > 1,672 at the level of significance 0,05 with the degree of freedom (df) 58. The alternative hypothesisi (Ha) is accepted. It point out that using guessing media themed local tourism is effective in teaching writing narrative text for the tenth grade students of SMA GKPI PAMEN.